The undefeated - Wayne, John, 1907-1979.; Hudson, Rock, 1925-1985.; Barrett, James Lee.; Twentieth Century-Fox Film Corporation; Fox Video (Firm) (Beberly Hills, Calif.. : Fox Video, 1992)
An action-packed western adventure about life after the Civil War. Yankee Colonel John Henry Thomas and Confederate Colonel James Langdon are enemies turned cohorts as they join forces in battling their way out of Mexico.
"1056."
Closed captioned for the hearing impaired.
Videocassette release of the 1969 motion picture by Twentieth Century-Fox Corporation.
Produced by Robert L. Jacks ; directed by Andrew V. McLaglen ; screenplay by James Lee Barrett ; music composed and conducted by Hugo Montenegro.
John Wayne, Rock Hudson, Tony Aguilar.
Keywords: Western films; Feature films; Videocassettes; United States -- History -- 1865-1898 -- Motion pictures